THE TECHNIQUE FOR MAKING AESTHETIC ACRYLIC RESIN REMOVABLE PARTIAL DENTURES IN AN ANTERIOR CROSS BITE CASE - Setyowati, Okti; Kusdarjanti, Endang; Sujati, Sujati; Inayati, Eny; Wahyuni, Sri; Laksmi Lita Rosa, Mia; Pratiwi, Nevy Istibasyarotul (Journal of Vocational Health Studies, 2022)
Background: Certain cases such as anterior cross bites require a different aesthetic removable denture technique from the conventional removable denture. Purpose: To provide an overview of a case about the technique of making aesthetic acrylic resin removable partial dentures for anterior tooth replacement in cases of anterior cross bite. Case analysis: The study examined the working model with maxillary and mandibular anterior cross bite cases. Result: The arrangement of artificial teeth was carried out as ideally as possible, so that it became harmonious. In this case, the incisal artificial teeth 11, 12, 21 were brought forward labially, so that an edge-to-edge position was formed with the opposing teeth. The clasp made was a half jackson which was placed on teeth 15 and 25, so that when the patient smiles the clasp is not visible to fulfill the aesthetic requirements. Conclusion: The technique of making aesthetic removable partial dentures in cases of anterior cross bite that has received more attention is the arrangement of the dental elements because it is different from the normal tooth arrangement. The artificial teeth were arranged in edge-to-edge bite position in order to obtain a harmonious occlusion while taking into account of the labial arch of the adjacent tooth as well as occlusion with the opposing tooth.